PERAN KADER REMAJA DALAM KEGIATAN POSYANDU REMAJA - Murniati Safitri; Netty Herawaty Purba; Aminah Aatinaa Adhyatma (Jurnal Ilmiah Kebidanan Imelda, 2025)
Adolescent cadres are adolescents who are selected or voluntarily volunteer and are trained to participate in implementing adolescent health services for themselves, their peers, their families and the community. The aim of this research is to determine the role of youth cadres as motivators, facilitators, communicators and promoters in youth posyandu activities. This research method is qualitative with a phenomenological approach. The research sample in this study consisted of 3 youth cadres, 3 teenagers, and 1 youth posyandu supervisor. The sampling technique in this research was nonprobability with a purposive sampling technique. This research was conducted at the Batu Selicin Lubuk Baja youth posyandu, Batam City. Data was collected by in-depth interviews. The results of this research showed that there was no role for teenage cadres as communicators in the activities of the Batu Selicin youth posyandu, Lubuk Baja, Batam City. The conclusion from this research is that teenage cadres have not optimized their role as communicators. This is because youth cadres are not provided with special training and youth cadres are also not given in-depth knowledge. This research can also be a reference for further research regarding the importance of youth cadre training.